Self-Control Examination of Blood Sugar Levels on Behavior Controlling Diabetes Mellitus - Wijayanti, Dewi; Noviyanti, Nur Indah; Manda, Hilda (Pancasakti Journal Of Public Health Science And Research, 2024)
Diabetes Mellitus is one of the five most important chronic conditions that affect life expectancy. If diabetes mellitus is not managed properly, it can cause various complications that can threaten life or life. If left untreated, Diabetes Mellitus complications can attack all parts of the body. Diabetes Mellitus is a hyperglycemic disease caused by cell insensitivity to insulin. Diabetes Mallitus (DM) is influenced by DM control behavior and one strategy to improve DM control behavior is to use self-control. The aim of this research is to self-control checking blood sugar levels so that respondents change their behavior to prevent diabetes mellitus control. This research is quantitative research with quasi-experimental pre-test and post-test design. Data was taken using a questionnaire where the research results showed a p-value of 0.001, which means that there is an influence of self-control in checking blood sugar levels on diabetes mellitus control behavior.